The effect of snakehead fish extract supplementation to first-line eradication regimen on macrophage migration inhibitory factor (MIF) expression in rats induced by Helicobacter pylori infection - Yulizal, OK; Lelo, Aznan; Ilyas, Syafruddin; Kusumawati, Raden Lia (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: This work was organized to assess macrophage migration inhibitory factor (MIF) expression in snakehead fish extract supplementation to first-line eradication regimen in rats induced by Helicobacter pylori infection. Materials and methods: A total of 28 manly rats were haphazardly isolated equally into four groups. Group-1 was the control negative, and groups-2–4 were H. pylori-infected groups. Group-2 was the control positive. Groups-3 and 4 were treated with first-line eradication regimen and first-line eradication regimen supplemented with snakehead fish extract, respectively. Immunoreactive scores (IRS) of MIF expression and eradication testing procedure were carried out. The comparison and difference between groups were analyzed by Kruskal–Wallis and post hoc Mann–Whitney U-test. A value of p < 0.05 was considered to be a limit of significance. Results: The average IRS of MIF expression in group-2 was the highest among other groups (p < 0.05). Group-4 (supplemented by snakehead fish extract) had a lower median value IRS of MIF expression compared to group-3 [1.0 (0.0–2.0) vs. 3.5 (2.0–6.0), p = 0.004]. Conclusion: MIF expression was higher in rats induced by H. pylori infection. Snakehead fish extract supplementation to first-line eradication regimen significantly reduces more MIF expression compared to a single administration of first-line eradication regimen in rats induced by H. pylori infection. Adv. Vet. Anim. Res., 7(2): 209-217, June 2020